2020
DOI: 10.21037/apm-20-2083
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and bone disorder biomarkers and inflammation indexes in patients with end stage renal disease

Abstract: Background: Chronic kidney disease (CKD) is an independent risk factor for bone and mineral metabolism disorder. Bone and mineral metabolism disorder develop gradually with the progression of renal failure. Various abnormalities include elevated fibroblast growth factor-23, decreased levels of 1,25-Dihydroxy Vitamin D (1,25-(OH)2D), and secondary hyperparathyroidism. This study aimed to evaluate the biomarkers and inflammation indexes of CKD-mineral and bone disorder (MBD), and to examine the associations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…In line with our findings, Szepietowski et al 11 recognized an inverse correlation between serum albumin levels and pruritus intensity score in HD patients. The association between lack of vitamin D administration and severe UP in the present study is a novel finding which is probably related to the amplified proinflammatory status in HD patients in the presence of low vitamin D levels 17 18…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In line with our findings, Szepietowski et al 11 recognized an inverse correlation between serum albumin levels and pruritus intensity score in HD patients. The association between lack of vitamin D administration and severe UP in the present study is a novel finding which is probably related to the amplified proinflammatory status in HD patients in the presence of low vitamin D levels 17 18…”
Section: Discussionmentioning
confidence: 62%
“…The association between lack of vitamin D administration and severe UP in the present study is a novel finding which is probably related to the amplified proinflammatory status in HD patients in the presence of low vitamin D levels. 17 18…”
Section: Discussionmentioning
confidence: 99%
“…Increased CRP is significantly associated with an increased risk of renal osteodystrophy in patients with CKD stages IV-V, according to another research [15]. Also, some research concluded the same thing with an adjusted p-value of 0.04 [16]. This relates to patients with renal osteodystrophy who undergo repeated hemodialysis, which can trigger an inflammatory response and increase CRP levels in patients with renal osteodystrophy [17].…”
Section: Discussionmentioning
confidence: 92%
“…PTH activates osteoblast and increases ALP level (28). Previous studies showed the positive association between the two variables in HD patients, but the strength of association differs according to i-PTH level (29,30). In addition, there were different results in the association between each variable and outcomes in HD patients.…”
Section: Discussionmentioning
confidence: 96%